Transnasal endoscopic surgery for selected orbital cavernous hemangiomas: Our preliminary experience. Issue 7 (19th June 2012) - Muscatello, Luca; Seccia, Veronica; Caniglia, Michele; Sellari–Franceschini, Stefano; Lenzi, Riccardo; Andersen, Peter
Abstract Background Endoscopic transnasal approaches to the orbit have been recently described and they have been proposed as an option in the surgical management of medial and inferior orbital lesions. Methods Retrospective evaluation of 3 patients operated on in our department during 2011 to remove a cavernous hemangioma of the inferior‐medial orbit. Two patients were operated on via an endoscopic transnasal approach and 1 patient was operated on via an external anterior approach. Results A complete surgical resection was obtained in all patients. A transient postoperative diplopia was recorded in the patient operated on via the external approach. No other significant complications were recorded. Conclusion Extraconal lesions adjacent to the paranasal sinuses can be safely removed through an endoscopic transnasal route. Intraconal lesions located inferiorly and medially to the optic nerve are amenable of transnasal endoscopic resection in selected cases. © 2012 Wiley Periodicals, Inc. Head Neck, 2013